Writing Poster at Higher Education: Victor Schwab Theory Analysis - Mega Febriani Sya; Fachri Helmanto (Wanastra: Jurnal Bahasa dan Sastra, 2020)
The management changing is started by an election of a new chairman. Supporting academic of the students, English lecturer assigns a project of poster creation of election using English. this research is to find what extent the poster is delivered to its audience. This study is qualitative research with an analytical descriptive as the method. The data are 5 English posters of Students’ election candidates. All of the posters are analyzed based on 5 criteria of Schwab’s good writing poster theory. Content analysis is used to validate the data findings. The study reveals all the 5 posters don’t meet the criteria. However, all of them gives similarity in showing advantage criterion. Next research should assess into a single poster to give a brief explanation of making a good poster.